The Gliadin and Casein Metabolism: Synthesis of Gliadomorphin and Casomorphin and Their Biological Consequences - Mr. MD.TANZIMUR RAHMAN TAMIM, Mr. MD.TANZIMUR RAHMAN TAMIM; Rashed Ahmed (RADINKA JAYA UTAMA PUBLISHER, 2025)
Gliadin (from gluten) and casein (from milk) are major dietary proteins that, upon incomplete digestion, yield biologically active opioid peptides known as gliadomorphin and casomorphin, collectively referred to as